Photobiomodulation for salivary gland dysfunction: aligning clinical expectations with etiology-dependent treatment responsiveness - Caio Camargo Calarga; Caio Bruno Tolentino de Brito; Cláudia Carrara Cotomácio; Alyne Simões (Lasers in Medical Science, 2026)
Abstract To discuss how distinct pathogenic mechanisms underlying salivary gland dysfunction may influence responsiveness to photobiomodulation (PBM) in patients with hyposalivation and xerostomia. A narrative review was conducted focusing on the biological and clinical factors potentially associated with PBM responsiveness across different etiologies of salivary gland dysfunction, including Sjögren’s disease, chemotherapy-induced dysfunction, radiation-induced salivary gland injury, and polypharmacy-associated hyposalivation. Mechanisms related to inflammation, oxidative stress, fibrosis, neurosecretory impairment, residual glandular viability, and persistence of etiological burden across different etiologies of salivary gland dysfunction were comparatively discussed. Therapeutic success assessments were also explored, emphasizing that symptom improvement and enhancement of oral quality of life may occur even in the absence of complete salivary flow normalization. In addition, the currently available evidence regarding PBM responsiveness in distinct etiological scenarios was critically presented, highlighting its heterogeneous and unbalanced distribution across conditions. Future directions involving biologically informed, individualized, and combination-based therapeutic approaches were also discussed. PBM responsiveness should not be interpreted as universally predictable across all etiologies of hyposalivation. Instead, therapeutic outcomes likely depend on several factors. Biologically informed and individualized approaches may contribute to more realistic therapeutic expectations and more personalized management strategies.